Dampak Mentoring Pada Keberhasilan Start-Up Business: Studi Kasus Pada Start-Up Business di Indonesia [Mentoring the Impact of Success of a Start-Up Business: A Case Study of a Start-Up Business in Indonesia] - Christina Yanita Setyawati (DeReMa (Development Research of Management): Jurnal Manajemen, 2016)
Entrepreneurship is a highly developed science today, as well as in the world of education in Indonesia. Teaching entrepreneurship at the university level, especially at some universities in Surabaya, the second largest city in Indonesia, shows the positive impact that there were 74.03% of start-up businesses that survived and thrived in 2014. Based on the previous observation, some business start-ups are accompanied by a mentor. Mentoring is a process of forming and maintaining lasting relationships that develop intensively among seniors with juniors. The mentoring function includes career and psychosocial functions. The main purpose of this research is to study the relationship between mentoring and the success of a start-up business. This study is a quantitative descriptive study using a random sampling method to obtain 100 samples. The tool used to collect data was a questionnaire. The methodology used to analyze the quantitative description to test the hypothesis. The results of this study indicate that mentoring influences the success of a start-up business that was owned by university students in Surabaya, Indonesia by 32% and 78% was influenced by other variables.